Oscillations and coherent radiation of harmonics in radiation spectrum of system of electrons moving in spiral in medium - Konstantinovich, A.V.; Konstantinovich, I.A. (Вопросы атомной науки и техники, 2011)
Using the Lorentz self-interaction method completing by Dirac hypothesis it is investigated the spectral distribution of the radiation power for the system of electrons moving along a spiral in transparent isotropic medium. The overlapping between neighbour harmonics as well as oscillations in the spectral distribution of one, two, three, and four electrons radiation power are studied for the case when the transversal component of electron velocity is bigger than the light phase velocity in medium but still less than the light velocity in vacuum. The effect of coherence in the spectrum of synchrotron-Cherenkov radiation for the system of two, three and four electrons is analyzed. Використовуючи метод сили самодії Лоренца, доповнений гіпотезою Дірака, досліджено спектральний розподіл потужності випромінювання системи електронів, що рухаются вздовж гвинтової лінії у прозорому ізотропному середовищі. Перекриття гармонік та осциляції у спектральному розподілі потужності випромінювання одного, двох, трьох і чотирьох електронів досліджено для випадку, коли поперечна компонента швидкості електрона більша від фазовоі швидкості світла у середовищі, але менша від швидкості світла у вакуумі. Досліджено ефект когерентності у спектрі синхротронно-черенковського випромінювання системи двох, трьох та чотирьох електронів. Используя метод силы самодействия Лоренца, дополненный гипотезой Дирака, исследовано спектральное распределение мощности излучения системы электронов, движущихся вдоль винтовой линии в прозрачной изотропной среде. Перекрытие гармоник и осцилляции в спектральном распределении мощности излучения одного, двух, трех и четырех электронов исследовано для случая, когда поперечная компонента скорости электрона больше фазовой скорости света в среде, но меньше скорости света в вакууме. Исследован эффект когерентности в спектре синхротронно-черенковского излучения системы двух, трех и четырех электронов.